PENGARUH UTANG LUAR NEGERI PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DAN KESINAMBUNGAN FISKAL INDONESIA PERIODE 1979-2009 - , Yohanes Maria Vianey Mudayen, S.P.d.; , Dr. Tri Widodo, M.Ec. Dev ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to analyze the influence of government foreign debt on economic growth and fiscal sustainability of Indonesia in 1979-2009. The research model used is cointegrating regression model with Ordinary Least Square (OLS) method and simultaneous equations model using Two Stage Least Square (TSLS). The results of cointegrating regression model and the first simultaneous equation model showed that the lag of government foreign debt has positive and significant impact on economic growth in Indonesia. Investment also has positive and significant impact on economic growth in Indonesia. However, savings interest rate of Central Bank and net exports have negative and significant effect on economic growth. The money supply is not significant effect on economic growth of Indonesia. Fiscal sustainability is derived from the equation reduced form and the primary balance has positive and significant impact on economic growth. The lag of government foreign debt has negative and significant effect on fiscal sustainability of Indonesia. Savings interest rate of Central Bank also have negative and significant impact on Indonesia's fiscal sustainability. However, economic growth comes from the reduced form equation has positive and significant impact on Indonesia's fiscal sustainability.